2019
DOI: 10.1021/acsami.9b06635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ion Diffusion in Cobalt Molybdenum Bimetallic Sulfide toward Electrocatalytic Water Splitting

Abstract: The electrocatalyst comprising two different metal atoms is found suitable for overall water splitting in alkaline medium. Hydrothermal synthesis is an extensively used technique for the synthesis of various metal sulfides. Time-dependent diffusion of the constituting ions during hydrothermal synthesis can affect the crystal and electronic structure of the product, which in turn would modulate its electrocatalytic activity. Herein, cobalt molybdenum bimetallic sulfide was prepared via hydrothermal method after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…An impressively low cell potential of 1.46 V at 10 mA cm −2 and 1.69 at 100 mA cm −2 , which is indeed noteworthy (CV curve is presented in Figure S18, Supporting Information). To the best of our knowledge, the NIS-450(foam)||NIS-450(foam) electrocatalyst system exhibits the lowest overpotential values reported for the transition metal-based sulfides as a bifunctional electrocatalyst for overall water splitting [16,20,21,23,24,[26][27][28][29][30][31][32][33][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Figure 5d). As expected, NIS-450(foam) shows two orders of magnitude higher C dl in comparison to the bare Ni foam (Figure S19, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An impressively low cell potential of 1.46 V at 10 mA cm −2 and 1.69 at 100 mA cm −2 , which is indeed noteworthy (CV curve is presented in Figure S18, Supporting Information). To the best of our knowledge, the NIS-450(foam)||NIS-450(foam) electrocatalyst system exhibits the lowest overpotential values reported for the transition metal-based sulfides as a bifunctional electrocatalyst for overall water splitting [16,20,21,23,24,[26][27][28][29][30][31][32][33][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Figure 5d). As expected, NIS-450(foam) shows two orders of magnitude higher C dl in comparison to the bare Ni foam (Figure S19, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, most of the recent works involve the exploitation of multi-metallic or multilayered sulfides, adding further complexity to the already cumbersome synthesis processes. [19,[24][25][26][27][28][29][30][31][32] In spite of tremendous efforts, economically scalable methods for industrial-scale production of morphologically and chemically-engineered earth-abundant binder-free electrocatalysts with low overpotentials for overall water splitting are still missing. Hence, there is an urge to quench the thirst for a bifunctional electrocatalyst, which not only displays low overpotentials but also qualifies the indispensable criterion of a simple and single step, rapid synthesis process at low temperatures (sub-500 °C) for economic scalability to industrial scales.…”
Section: Introductionmentioning
confidence: 99%
“…There are continuous investigations on the use of active transition elements like Ni, Co, Fe, Cu, and Mo and their combinations with sulphur as electro catalysts. Some varieties include Co–Ni–S, 26–29 Cu–Co–S, and Cu–Mo–S, 30–32 Co–Fe–S, 33–37 Co–Mo–S, 38 and Zn–Co–S. 39 The ternary chalcogenides have shown superior properties like high electrical conductance than monometallic due to the low activation energy for electron transfer between cations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, earth‐abundant transition‐metal‐based catalysts gradually emerge as the attractive substitute of noble metal catalysts due to its abundant resources, low cost, and excellent catalytic performance. [ 21–25 ] As a kind of key transition metal catalyst, bimetallic sulfide [ 26–28 ] shows impressively improved catalytic performances benefiting from the synergistic effect [ 29,30 ] of the multiple oxidation states and much richer active sites compared with the single metal sulfide catalyst. [ 31,32 ] As a representative of bimetallic catalyst, Co 2− x Ni x O 2 nanosheets have been successfully used as active and stable electrocatalysts to split water by Li et al [ 33 ] In addition, NiCo 2 S 4 /N,S codoped reduced graphene oxide is reported to efficiently catalyze the water splitting reaction with high stability.…”
Section: Introductionmentioning
confidence: 99%